(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2017)
A wide spectrum of dural lesions occurs which is mimicking meningioma. The meningeal haemangiopericytoma is a rare tumor of meninges that is difficult to distinguish from meningioma; however both are treated similarly with surgical resection with or without radiotherapy to reduce the risk of recurrence. Macroscopically many haemangiopericytoma resemble to meningioma but are distinct histologically. These tumors show more aggressive natural history. Vascular nature of tumor suggests a different therapeutic approach thus fore warning a surgeon to a potentially more challenging resection. Journal of National Institute of Neurosciences Bangladesh 2015;1(2): 69-71